A machine learning-based exploration of resilience and food security - Villacis, Alexis H.; Badruddoza, Syed; Mishra, Ashok K. (Applied Economic Perspectives and Policy, 2024)
Leveraging advancements in remote data collection and using the Food Insecurity Experience Scale (FIES) as a proxy measure of resilience, we show that machine learning models (such as Gradient Boosting Classifier, eXtreme Gradient Boosting, and Artificial
Keywords: Ethiopia; Food Insecurity Experience Scale; Malawi; Nigeria; Uganda; Predictive Performance